A 7-point evidence-based care discharge protocol for patients hospitalized for exacerbation of COPD: consensus strategy and expert recommendation - Sundeep Salvi; Deesha Ghorpade; Sanjeev Nair; Lancelot Pinto; Ashok K. Singh; K. Venugopal; Raja Dhar; Deepak Talwar; Parvaiz Koul; Pralhad Prabhudesai (npj Primary Care Respiratory Medicine)
Abstract Acute exacerbations of COPD (ECOPD) are an important event in the life of a COPD patient as it causes significant deterioration of physical, mental, and social health, hastens disease progression, increases the risk of dying and causes a huge economic loss. Preventing ECOPD is therefore one of the most important goals in the management of COPD. Before the patient is discharged after hospitalization for ECOPD, it is crucial to offer an evidence-based care bundle protocol that will help minimize the future risk of readmissions and death. To develop the content of this quality care bundle, an Expert Working Group was formed, which performed a systematic review of literature, brainstormed, and debated on key clinical issues before arriving at a consensus strategy that could help physicians achieve this goal. A 7-point consensus strategy was prepared, which included: (1) enhancing awareness and seriousness of ECOPD, (2) identifying patients at risk for future exacerbations, (3) optimizing pharmacologic treatment of COPD, (4) identifying and treating comorbidities, (5) preventing bacterial and viral infections, (6) pulmonary rehabilitation, and (7) palliative care. Physicians may find this 7-point care bundle useful to minimize the risk of future exacerbations and reduce morbidity and mortality.